Action-projection in Japanese conversation: topic particles wa, mo, and tte for triggering categorization activities - Tanaka, Hiroko (Frontiers in Psychology, 2015)
Conversation analytic work has revealed how anticipatory completions and preemptive actions can offer invaluable glimpses into the cognitive, contextual, grammatical, and temporal bases of projectability in turn-taking, by virtue of their potential not only as a display of participants' online prediction of roughly what it might take to complete a turn-in-progress but also to plan the next move. While the predicate-final word order and the incremental transformability of turns in Japanese generally lead to delayed projectability of turn-endings, this may be partially offset by the capacity of certain postpositional particles to trigger and propel prospective action trajectories. This article engages in a case study of the topic particle wa (and related particles mo and tte), by demonstrating how its grammatical affordances, the categorization activities, and cognitive processing it can set in motion, coupled with the immediate contextual, and temporal-productional features may coalesce to a point of critical mass, thereby enhancing the projectability of the not-yet-produced trajectory of the current turn. The discussion attempts to contribute to recent debates on ways language-specific lexicogrammatical resources are deeply interlinked with the types of opportunities that are provided for social action.